2018
DOI: 10.14710/dijb.1.2.2018.112-120
|View full text |Cite
|
Sign up to set email alerts
|

Organizational climate, organizational commitment, job satisfaction, and employee performance

Abstract: The purpose of this study was to examine the relationship between organizational climate, organizational commitment,  job satisfaction, and employee performance. Particularly, we examine the effect of organizational climate and organizational  commitmenton job satisfaction. Furthermore, we also test the effect of job satisfaction on employee performance.Results of path analysis on 90 respondents showsopports for all hypotheses. Partially, organizational climate and organizational commitment have positive effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 18 publications
3
13
0
3
Order By: Relevance
“…The results of this study indicate that work commitment has a significant positive effect on work performance, so hypothesis 3 which states that work commitment (affective, normative, and continuing) is acceptable. The better work commitment can also affect the improvement of work performance, this is supported by the results of previous studies, namely Setyaningtyas et al (2013), Lotunani et al (2014), Bandula and Jayatilake (2016), Gunawan et al (2017), Renyut et al (2017), Sugihartono (2018), Paramita et al (2018), Hidayah and Tobing (2018), Metin and Asli (2018), and Sungu et al (2019).…”
Section: Hypothesis Testingsupporting
confidence: 60%
See 2 more Smart Citations
“…The results of this study indicate that work commitment has a significant positive effect on work performance, so hypothesis 3 which states that work commitment (affective, normative, and continuing) is acceptable. The better work commitment can also affect the improvement of work performance, this is supported by the results of previous studies, namely Setyaningtyas et al (2013), Lotunani et al (2014), Bandula and Jayatilake (2016), Gunawan et al (2017), Renyut et al (2017), Sugihartono (2018), Paramita et al (2018), Hidayah and Tobing (2018), Metin and Asli (2018), and Sungu et al (2019).…”
Section: Hypothesis Testingsupporting
confidence: 60%
“…The results of a study of a number of studies found that work competence influences employee work commitment (Lotunani et al, 2014;Setyaningtyas et al, 2013;Suriadi et al, 2018). On the other hand, work commitment also influences job performance (Setyaningtyas et al, 2013;Lotunani et al, 2014;Bandula & Jayatilake, 2016;Gunawan et al, 2017;Renyut et al, 2017;Sugihartono, 2018;Paramita et al, 2018;Hidayah & Tobing, 2018;Metin & Original, 2018). A number of studies also found that work commitment significant as a mediator in the relationship of work competence to work performance (Bandula & Jayatilake, 2016;Renyut et al, 2017;Sugihartono, 2018).…”
Section: Work Commitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Organizational climate has negative and insignificant effect on employee performance, which means that there is no impact in organizational climate towards employee performance.The employee performance does not affected by the organizational climate which is the behavior of the employee does not influence by the situation or climate of the organization (Raja et.al., 2019;Diputra, 2018;Sugiarto, 2018;Utami & Nusraningrum, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…given badly it will also decrease the employee performance of the employee. This finding is supported by previous research (Raja et.al., 2019;Diputra, 2018;Sugiarto, 2018). The employee perspective of the organization quality will effect to organizational climate and will subsequently impact to the employee's next behavior.…”
Section: Methodsmentioning
confidence: 99%